THE SUBTROPICAL LOWER WATER BETWEEN THE PHILIPPINES AND IRIAN (NEW GUINEA) - Wyrtki, Klaus (Marine Research in Indonesia, 1956)
Oceanographic observations are published, taken by the research vessel Siboela in 1949 at 57 stations in the Celebes Sea and around Halmahera. Basing on these observations, an analysis is made of the Subtropical Lower Water (salinity-Maximum) in this region and is compared with the observations of the Snellius and the Dana in 1929. The distribution of the oxygen content allows a distinction of the Lower Water into a northern and a southern water type, which regions of origion are situated in 23°N between 165°E and 165°W and in 15°S between 120° and 150°W respectively. It is shown that the temperature of the salinity maximum in 1949 is 1.4° higher and the salinity 0.11? lower than in 1929. The topography of the salinity maximum, which lies in about 100 to 200 m, is closely correlated with the surface currents.